Greece's new geopolitics - Lesser, Ian O., 1957- (Rand, 2001)
This work assesses Greece's evolving geopolitical role in light of its developing international relationships and a challenging regional political environment. It pays special attention to the implications for southeastern Europe and transatlantic relations.